Assessment of Potential Ecotourism Site in Xaisomboun, Central Laos - Buaxaiya, S.; Phompila, C.; Phengsopha, K.; Chanthavong, B.; Nanthavongduangsy, K.; Thongmanivong, S.; Baral, H. (Scientific Research Publishing, Inc., 2021)
Appropriate ecotourism planning is crucial for sustainable ecotourism development in developing countries including Laos. The primary objective of this research was to identify the potential sites for ecotourism in order to assist in planning and decision making to ensure the sustainable natural forest resource management. GIS data analysis was undertaken to assess the potential sites for ecotourism. We used seven factors describing biophysical characteristics; forest cover, water, elevation, slope, proximity to village, road accessibility and historical attractive sites. It was found that there is around 1200 ha of the entire area of Xaisomboun province which is the most suitable for inland recreational activities, about 1980 ha for beautiful ecological sceneries, roughly 1143 ha for historical tourism activity sites, and finally 1031 ha of a total area that most suitable for multipurpose ecotourism activities. These most suitable areas are located mostly in the protected areas, dense forests and high value of natural resources. These are also major attractions for historical and country revolutions. There is a need to incorporate appropriate infrastructures and local engagement and services. The result is useful for ecotourism development and great benefit in terms of sustainable social-economic development, conservation of biodiversity and other ecosystem services.